Perancangan dan Kawalan Pembangunan di Sarawak : Kajian Kes Majlis Daerah Sarikei - Noni Harianti, Junaidi (2004)
Sarawak's development planning practice is said to be unique compared to other states in Peninsular Malaysia. Generally, this research is done to identify the planning practices and development control tools in Sarawak and focusing in Sarikei Division. This research is also looking at centralization processes being done by the State Authorities toward local authority in Sarikei. Other than that, this research also looks at considering factors and problems which arise during planning and controlling stages. The sample group method is conducted in this research. Firstly, respondents who include the government agencies and departments as well as developers were randomly selected. Quantitative and qualitative approach applied to analyze the findings. The research finding shows that Sarawak state practices decentralization in their development projects. However, the state still controls certain processes and authority sanction the project leaving the local authority to sanction the project leaving the local authority less empower regarding on that matter. The planning and controlling stages of environment, physical, types of development and politics. The factors that hinder the development in Sarikei were strict registration process, long sanctioning period, shortcomings at the local authority management level and lack of complete project. Hopefully, this research may able to solve the problems faced during planning and controlling stages in Sarawak, particularly Sarikei.